Structured and Unstructured Email Writing Skill: A Study of Nepali Students - Ramesh Prasad Adhikary (Budapest International Research and Critics University, 2022)
The main objective of the present study is to compare structured and unstructured email writing skills among Nepali students. This study explores the common mistakes on email writing of Nepali students of Higher Secondary School. The data was collected from 30 students of Class XI and XII of GVN School, Nepalgunj (Nepal). They were in two structured and unstructured group. They were asked to send email and collected the samples for data analysis. They were also asked to fill the questionnaire via Emo. From the data analysis, they had some common mistakes on format and grammar on Email writing and they have certain discourse-specific thematic pattern on email writing the research found that there is significant difference between structured and unstructured groups in Email writing skills.